A crossover clinical trial to assess the effectiveness of different oral hygiene regimens on the reduction of morning bad breath in healthy young adults - Charu Khurana; Shourya Tandon; B R Chinmaya (Wolters Kluwer Medknow Publications, 2018)
Context: Bad breath causes embarrassment and affects interpersonal social communication. Morning breath odor is a commonly encountered oral problem which should be rectified with effective oral hygiene measure. Aim: The aim of this study was to assess and compare the effectiveness of different oral hygiene regimens on the reduction of morning bad breath, plaque formation, and gingivitis in healthy young adults. Settings and Design: A four-step, crossover clinical trial was conducted among 40 young adults aged 18-22 years residing in one of the nongovernmental organizations in New Delhi. Materials and Methods: Study participants were divided into four groups, which underwent intervention for 7 days each. Group 1: tooth brushing; Group 2: tooth brushing and mouthwashing; Group 3: tooth brushing and tongue scraping; and Group 4: combination of all. A washout interval of 14 days was employed in between the groups. Breath scores were measured at three time intervals whereas oral health status was recorded at the beginning and the end of each interventional period. Statistical Analysis Used: Appropriate tests such as paired t-test, ANOVA test, and Pearson correlation tests were used in the study. Results: The highest reduction in mean value of breath scores (2.03 ± 0.69) was found in Group 4 followed by Group 3. Similarly, Group 4 showed the highest reduction in mean value of plaque score (0.79 ± 0.19) and gingival score (0.54 ± 0.23) followed by Group 2. Conclusion: Combination of mechanical and chemical oral hygiene measures is an effective regimen for the reduction of morning bad breath.